Improving company competitive advantage through transformational leadership and the Pro-Growth Orgware quality - Suhendri; Absah, Yeni; Siahaan, Elisabet; Sirojuzilam (International Journal of Management and Sustainability, 2023)
This study examines the significance of the Resource-Based Theory in assessing the competitive advantage of a corporation. The purpose of this study is to examine the correlation between transformational leadership and the effectiveness of pro-growth organisational software in affecting this advantage. A total of 433 participants from plantation-holding firms in Indonesia completed a questionnaire. The data analysis in this study utilized the structural equation modelling feature of LISREL 8.8. The findings of the study indicate that the introduction of Pro-Growth Orgware does not have an immediate effect on its quality. However, it was observed that the implementation of transformational leadership practises has a positive influence. Nevertheless, the use of Pro-Growth Orgware significantly enhances the competitive advantage of the organisation. According to the Resource-Based Theory, interactions between value-oriented development and resource augmentation provide the basis for competitive advantage. Understanding the interactions between resources, capabilities, competitive advantage, and profitability crucial for maintaining competitiveness is at the core of this theory. The results highlight Pro-Growth Orgware’s dynamic capability, essential for developing new goods and procedures to increase competitive advantage.